Moderate Fever Cycles as a Potential Mechanism to Protect the Respiratory System in COVID-19 Patients - Guihur, Anthony; Rebeaud, Mathieu E.; Fauvet, Bruno; Tiwari, Satyam; Weiss, Yoram G.; Goloubinoff, Pierre (Frontiers in Medicine, 2020)
Mortality in COVID-19 patients predominantly results from an acute respiratory distress syndrome (ARDS), in which lungs alveolar cells undergo programmed cell death. Mortality in a sepsis-induced ARDS rat model is reduced by adenovirus over-expression of the HSP70 chaperone. A natural rise of body temperature during mild fever can naturally accumulate high cellular levels of HSP70 that can arrest apoptosis and protect alveolar lung cells from inflammatory damages. However, beyond 1-2 hours of fever, no HSP70 is further produced and a decreased in body temperature required to the restore cell’s ability to produce more HSP70 in a subsequent fever cycle. We suggest that antipyretics may be beneficial in COVID-19 patients subsequent to several hours of mild (<38.8°C) advantageous fever, allowing lung cells to accumulate protective HSP70 against damages from the inflammatory response to the virus SARS-CoV-2. With age, the ability to develop fever and accumulate HSPs decreases. This could be ameliorated, when advisable to do so, by thermotherapies and/or physical training.